Community resilience in the community plantation forest program: Analysis on Muna Island, Southeast Sulawesi, Indonesia - Arniawati, Arniawati; Awang, San Afri; Suryanto, Priyono; Rohman, Rohman (Journal of Degraded and Mining Lands Management, 2025)
This study explicitly captured how the existence of local wisdom interacts with the challenges of implementing community plantation forest programs, which often overlook traditional practices but can lead to changes in deforested land. Data on land cover change, a leading indicator, were obtained from the analysis of Landsat 7 and Landsat 8 satellite imagery, drone observations, and field surveys. Information about the practice of local wisdom in using CPF permit areas in the KPHP Unit VI Muna Island area was collected through in-depth interviews with the community. The forest cover classification was performed using ArcGIS 10.8 software, which combined on-screen digitization with field verification to ensure the accuracy of the satellite imagery data. The analysis results showed significant changes in forest cover during the four observation periods (2010-2022). Notably, there was a significant increase in land use for mixed gardens, accounting for up to 70.29% of the total area. This aligns with kaindea's practice of combining woody plants (forestry and plantations). Meanwhile, dryland and mixed dryland farming decreased to 4.17% and 25.55%, respectively. This practice can create a forest-like landscape that maintains the balance of the karst ecosystem and supports the family economy. These findings not only fill knowledge gaps regarding the integration of karst region-specific local wisdom in social forestry programs but also offer an adaptive model of forest management that can be replicated in similarly vulnerable ecosystems. Integrating local wisdom in vulnerable areas such as karst has proven to be a catalyst in sustainable forest management.